2014
DOI: 10.3111/13696998.2014.953680
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the burden of illness from cervical dystonia using the Toronto Western Spasmodic Torticollis Rating Scale scores and health utility: a meta-analysis of baseline patient-level clinical trial data

Abstract: This study was able to define TWSTRS scores in patients with CD in terms of associated utility. This approach could help in capturing the disease's burden through measures that are more tangible than TWSTRS scores to patients, carers, clinicians, and healthcare payers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Of note, the relatively unrestrictive entry criteria to the observational studies allowed us to include subjects with a broader spectrum of disease than most RCTs. This is highlighted by lower mean TWSTRS Total scores (33.95 in the present analysis vs. 43.23 in RCTs) [ 25 ], supporting the idea that RCTs often recruit subjects with more severe disease [ 25 ]. Moreover, we also observed that most patients presented with a complex pattern of dystonic movements and the majority had additional components of shoulder elevation, tremor and/or jerk.…”
Section: Discussionsupporting
confidence: 70%
“…Of note, the relatively unrestrictive entry criteria to the observational studies allowed us to include subjects with a broader spectrum of disease than most RCTs. This is highlighted by lower mean TWSTRS Total scores (33.95 in the present analysis vs. 43.23 in RCTs) [ 25 ], supporting the idea that RCTs often recruit subjects with more severe disease [ 25 ]. Moreover, we also observed that most patients presented with a complex pattern of dystonic movements and the majority had additional components of shoulder elevation, tremor and/or jerk.…”
Section: Discussionsupporting
confidence: 70%
“…The EQ-5D was not directly administered to patients. Instead, it was calculated from a simple mapping algorithm described in a previously published paper (see Jen et al 2014), which estimated the linear association between the TWSTRS total score and EQ-5D health utilities [17]. CD patients in the Jen study were administered both the TWSTRS, and the Short Form-36 (SF-36) Health Survey.…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses of BT and more local injections are needed for complex forms of CD. Initial dose of 500 IU of Dysport ® can be increased if needed 16 . In our patients initial dose of 500 IU was sufficient to provide good therapeutic response.…”
Section: Tablementioning
confidence: 99%